(untitled) (Acta Scientiarum. Biological Sciences, 2016)
A. muscoides (Rhodophyta) has three polysulfated fractions (-1, -2 and Am-3). Am-2 displayed anti-inflammation and serpin-independent anticoagulation effects; however, no effect of oligomers on thrombin-generation (TG) has been demonstrated. This study employed mild-acid hydrolysis to obtain low-molecular-size derivatives from Am-2 and compared in vitro inhibitory effects between intact Am-2 and its hydrolysates on a TG assay. The polysaccharidic extract was fractionated by DEAE-cellulose that revealed Am-2 eluted with 0.75-M NaCl containing sulfate (23%), hexoses (51%) and absence of proteins, and indicating, by one-dimension nuclear magnetic resonance, structure of galactan similar to that of the extract. The depolymerization with HCl (0.02 or 0.04-M, 60°C) for different times progressively reduced the charge density and the molecular-size of Am-2 based on electrophoresis in agarose and polyacrylamide gels, respectively, where at higher acid concentration and critical time up to 5h yielded fragment of Ì´ 14-kDa similar to that of unfractionated heparin (UHEP). Regarding the TG assay, intact Am-2 inhibited concentration-dependent intrinsic pathway, whereas its hydrolysates abolished it like UHEP, except the analog fragment (92.87% inhibition), when in 60-fold diluted human plasma using chromogenic method in a continuous system. The results reveal an alternative approach for the production of oligosaccharides from A. muscoides with TG inhibition.